EMPIRICAL STUDY: PERFORMANCE ANALYSIS BASED ON COMPETENCY, COMMITMENT AND EMPLOYEE WORK CONTRIBUTION - Abd. Rasyid Syamsuri (SEAN Institute, 2022)
This study uses empirical data to evaluate employee performance in terms of their competence, commitment, and work contrinution. 60 employees of PT. Isuindomas Putra, Medan is the population of this study. Quota sampling is the sampling method used, with the entire population serving as the research sample. With a t-statistic value of 4.014 and an overall coefficient of influence of 0.480, the findings indicated that competence had a positive and significant impact on employee performance. With a t-statistic of 0.196 and a total effect coefficient of 0.043, commitment has a positive but not significant impact on employee performance. With a t-statistic value of 3.088 and an overall coefficient of influence of 0.482, the work contribution has a positive and significant impact on employee performance. The findings of the structural model test also show that employee performance has an adjusted R square value of 0.904, which indicates that competence, commitment, and work contribution can account for 90.4% of employee performance.